Phase I trial of systemic intravenous infusion of interleukin‐13‐Pseudomonas exotoxin in patients with metastatic adrenocortical carcinoma. (13th March 2015) - Liu‐Chittenden, Yi; Jain, Meenu; Kumar, Parag; Patel, Dhaval; Aufforth, Rachel; Neychev, Vladimir; Sadowski, Samira; Gara, Sudheer K.; Joshi, Bharat H.; Cottle‐Delisle, Candice; Merkel, Roxanne; Yang, Lily; et al.
<x xml:space="preserve">Abstract</x> This Phase I dose‐escalation trial determined that interleukin‐13‐Pseudomonas exotoxin (IL‐13‐PE) could be safely administered via systemic intravenous infusion at 1 μg/kg in patients with metastatic adrenocortical carcinoma. However, patients developed high levels of neutralizing antibodies during the treatment, which suggested that in future clinical trials strategies for immunodepletion before IL‐13‐PE treatment should be considered.<boxed-text content-type="graphic" id="cam4449-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>